The value of fruits and nuts in the dietary - Brenner, Viva (My University, 1904)
Introduction: In the earliest records of history the diet of people consisted largely of fruits and nuts, and as a result we find they were strong physically, mentally and morally when they partook of such a diet. We have an illustration in the antediluvians who lived for hundreds of years. The early Greeks and Romans subsisted largely on bread and fruit. They were powerful in physical strong too as well as having the greatest minds. They built large cities, and were the rulers of the world, but when they indulged in luxuries and rices came their downfall Fruit eating races are noted for their bright educated and intelligent minds It has been said that “fruit happiness and longevity go together.” To make progress toward high moral and physical development one must partake largely of fruits, which should be mingled with the other diet.
Citation: Brenner, Viva. The value of fruits and nuts in the dietary. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Diet; Fruit; Nuts; History of Diet; Produce; Theses; Manuscripts (documents)